أهمية الصناعات التحويلية السعودية : دراسة جغرافية تحليلية - الغمري، سامي صلاح عبدالله (جامعة الملك عبدالعزيز, 2012)
تمثل الصناعة في المملكة العربية السعودية أحد الخيارات المتاحة لاستثمار إيرادات النفط في قطاعات اقتصادية منتجة تحافظ على قيمة الإيرادات من جهة، وعلى توسيع القاعدة الإنتاجية من جهة أخرى، مما يقلل من اعتماد الاقتصاد السعودي على الاستيراد الخارجي ويقلل بالتالي من مخاطر التبعية الاقتصادية في مرحلة ما بعد النفط. هذا ولاشك أن تنمية قطاع الصناعة من شأنه المساعدة الفاعلة على نمو قطاعات الاقتصاد الوطني الأخرى انظر لما للتصنيع من أهمية في حياة الاقتصاد وتنقسم الصناعات التحويلية السعودية إلى قسمين: \ 1-\ صناعات ذات استخدام مكثف لأرس المال والتقنية الصناعية المتقدمة (وهي الصناعات الكيماوية الأساسية). \ 2-\ صناعة تحويلية خفيفة كصناعات المواد الغذائية والمشروبات، وصناعة مواد البناء والخزف والزجاج، وصناعة المنتجات البلاستيكية وصناعة المنسوجات والملابس والصناعات الجلدية ومنتجاتها وصناعة الورق ومنتجاته، وصناعة الأثاث والخشب ومنتجاته وصناعة منتجات المعادن اللافلزية وغيرها. \ بلغ عدد المصانع المنتجة في المملكة العربية السعودية، ما مجموعه 4513 مصنعًا، فيما بلغ عدد العمالة الصناعية 503.469 عاملاً، وبلغ إجمالي التمويل الصناعي حوالي 400 مليار ريال وبلغت مساهمة قطاع الصناعة في الناتج المحلي عام 2009م/ 1430ه حوالي 6,12%. \ كل هذه المؤشرات شجعت الباحث على القيام بهذه الدراسة الجغرافية التحليلية لهذا القطاع الاقتصادي المهم. وقد اختتمت الدراسة بالنتائج، التي كان من أبرزها وجوب تنمية قطاع الصناعة التحويلية ودعمه من قبل الدولة، وبموجب هذا الدعم والتنمية لهذا القطاع ستأخذ المملكة مكانها في نهاية العقد الحالي (2010 -2020م) كأحد نمور الصناعة العربية. Manufacture in the Kingdom of Saudi Arabia represents one of the options available to invest oil revenues in the economic sectors to preserve value of revenue on one hand, and to expand the industrial production base on the other hand, reducing the dependence of the Saudi economy on import from external resources, and thus reduce the risk of economic dependency at the non oil era. Development of industry would actively help the growth of other sectors of the national economy Saudi Manufacture is divided into two parts: \ 1- Extensive industry: using extensive capital and advanced industrial technology e.g. chemical products. \ 2- Light manufacturing industry e.g. food and beverages, building materials, plastic products industry, which depend mainly on the products of chemical industries as raw materials, also textiles, clothing and leather industries, paper industry, manufacture of furniture and wood products and non-metallic mineral products industry and etc. \ The number of the productive factories reached 4513, while the total number of industrial employment 503469 labors, and total industrial funding of about 400 billion riyals, and the contribution of the industrial sector in GDP in 2009/1430 about 12.6%. \ All these indicators have encouraged the researcher to undertake this geo-analytical study. Having concluded the study results, with the most prominent that the development of the manufacturing sector by the state, under the support and development funds will highlight the Kingdom at the end of the current decade (2010 2020) as one of Arabian leopards if the state priority continues given the support and development to this sector.
Keywords: الاقتصاد الصناعى -- الصناعات التحويلية -- الصناعات التحويلية السعودية -- التركز الصناعى -- النمو الصناعى -- التمويل الصناعى -- المملكة العربية السعودية